The Effect of E-commerce Platforms, Digital Marketing, and User Experience on Market Reach and Competitiveness of Indonesian MSMEs - Wijayanto, Gatot; Jushermi, Jushermi; Nursanti, Aida; Novandalina, Arini; Rivai, Yutiandry (International Journal of Business, Law, and Education, 2024)
The complex relationships between digital marketing tactics, user experience, and e-commerce platforms are examined in this study, as well as how these relationships affect MSMEs' (micro, small, and medium-sized enterprises) ability to compete in the Indonesian market. Structural Equation Modeling with Partial Least Squares (SEM-PLS) is utilized in the study to analyze survey data obtained from 150 MSMEs in Indonesia. The adoption of e-commerce and market reach, competitiveness and effective digital marketing techniques, and user experience and overall market performance are all significantly positively correlated, according to the results. The report offers detailed insights into the digital tactics influencing MSMEs' success in the Indonesian business environment. It also offers recommendations for further research and real-world applications for companies and regulators.